Initiative huronne-wendat de création d'une aire protégée : mobilisation des savoirs et affirmation territoriale - Cyr, François-Xavier (Université Laval, 2016)
This study analyzes the Ya’nienhonhndeh protected area project of the Huron-Wendat First Nation. Through the exploration of the production, the circulation and the application of the knowledges associated with this project, I seek to shed light on the constituting dynamics of the relations between the Huron-Wendat and the Quebec state regarding the former’s traditional territory, the Nionwentsïo. This study first aims to expose the Huron-Wendat’s aspirations regarding the future of their traditional territory while documenting the knowledges produced to assert these aspirations. Then, from a cartography built on the circulation of these knowledges, I elucidate the bureaucratic and institutional obstacles blocking the realization of the Huron-Wendat’s aspirations. Finally, based on the observation of the applications made of these knowledges, I broaden my reflection on the power relations existing between the Huron-Wendat First Nation and the Quebec state regarding the Nionwentsïo. Key words : protected area, Huron-Wendat, project, aspirations, First nations, bureaucracy, institutions, power relations, Quebec state Ce mémoire traite du projet de création de l’aire protégée Ya’nienhonhndeh de la Nation huronne-wendat. À travers l’exploration de la production, de la circulation et de l’utilisation des savoirs relatifs à ce projet, nous cherchons à éclairer les dynamiques constitutives des relations entre la Nation huronne-wendat et l’État québécois dans le cadre de la gestion du territoire traditionnel huron-wendat, le Nionwentsïo. Ce mémoire vise d’abord à mettre en lumière les aspirations de la Nation huronne-wendat concernant l’avenir de son territoire ancestral ainsi qu’à documenter les types de savoirs produits pour les faire valoir. Ensuite, à partir de la cartographie du cheminement de ces savoirs, sont exposés les obstacles structurels qui entravent la réalisation de ces aspirations lorsqu’elles doivent passer par la bureaucratie québécoise. Puis, en s’appuyant sur quelques-unes des diverses utilisations ...